The reliability of the i-STAT clinical portable analyser - Dascombe, B. J.; Reaburn, P. R. J.; Sirotic, A. C.; Coutts, A. J. (Journal of Science and Medicine in Sport, 2007)
The purpose of this investigation was to assess the reliability of the i-STAT clinical portable analyser and CG4+ cartridge measures of blood pH, partial pressures of O2 (pO2) and CO2 (pCO2), bicarbonate ([HCO3-]), base excess (BE), total carbon dioxide (TCO2), oxygen saturation (sO2) and blood lactate ([BLa-]) at various exercise intensities. A comparison between [BLa-] measured by the i-STAT and the Accusport lactate analysers during an intermittent treadmill run was also undertaken. The technical error of measurement (TEM%) at rest, at moderate (200 W) and maximal exercise () was acceptable (<15%) for all parameters. The intra-class correlation coefficients for each analyte ranged from weak-to-strong across resting (ICC = 0.19-0.96) and moderate (ICC = 0.30-0.96) exercise intensities. The ICC for all analytes were observed to be strong following maximal intensity exercise (ICC = 0.77-0.95). The comparison of the [BLa-] measures between the i-STAT and Accusport showed that the difference between measures was acceptable at both low (<4 mmol L-1) (-0.39 ± 0.27 mmol L-1), moderate to high concentrations (>4 mmol L-1) (0.58 ± 1.22 mmol L-1), and across all [BLa-] data (0.36 ± 1.13 mmol L-1). In conclusion, the i-STAT clinical analyser and CG4+ cartridge provides reliable measures of a number of blood parameters across exercise intensities. The [BLa-] measures from the i-STAT analyser are consistent with that of the Accusport lactate analyser.